Variations in mechanical wood properties of half-sibling genetic families of black alder [Alnus glutinosa (L.) Gaertn.] - Šilinskas, Benas; Varnagirytė-Kabašinskienė, Iveta; Beniušienė, Lina; Aleinikovas, Marius (Frontiers in Materials, 2024)
The study investigated the wood mechanical properties of black alder (Alnus glutinosa (L.) Gaertn.), a widely distributed deciduous tree in Europe valued for its suitability in silviculture and wood industry applications. The aim was to compare these properties among selected half-sib families and assess the relationship between wood hardness and other characteristics. Experimental plantations of black alder progenies from Lithuanian populations were established in different forest regions in 1998. The study analyzed various parameters for different genetic families, including tree diameter, height, wood hardness, moisture content, wood density, and mechanical properties.The findings revealed significant variability in wood properties among half-sib families, highlighting a strong genetic influence. While the static modulus of elasticity showed no notable difference across families, other properties showed significant variations.Furthermore, the analysis identified weak correlations between wood hardness and other mechanical properties like density, modulus of elasticity, and bending strength. This suggests that wood hardness may not reliably indicate wood quality for industrial applications. Consequently, the study recommends considering alternative nondestructive properties, such as dynamic modulus of elasticity, in future genetic studies of black alder for more accurate assessments of wood quality.